Intelligent Automobiles Diagnostic System - Mohannad O. Rawashdeh, Sayel M. Fayyad, Sulieman Abu-Ein, Waleed Momani, Zaid Abulghanam, A. M. Maqableh (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The goal of smart or intelligent car diagnostics systems is to provide access to car problems more accurately and easily than traditional systems, and there is a group of drivers who do not know the timing of the periodic diagnosis of the car, for example (when to change the spark plug or change different types of filters), and when the driver does not pay attention to the importance of the periodic maintenance schedule, malfunctions occur at random times, for example, if an engine problem occurs and the maintenance team is unaware of the problem, other issues may arise when the Check Engine light illuminates. This paper aims to eliminate all of these issues by sending notifications to the driver's mobile phone about the time of periodic maintenance for each piece, which can be for the allowance after a certain time or some distance, and changing the driver in the event of an engine problem and how to maintain it. It was found that the suggested system is efficient in decreasing sudden damage occurred in automobiles system by providing on time messages and warnings to the driver about systems need maintenance which enhances the preventive maintenance of automobiles.